Developing an Environmental Impact Assessment for Floating Island Applications - Tamis, Jacqueline E.; Jongbloed, Ruud H.; Piet, Gerjan J.; Jak, Robbert G. (Frontiers in Marine Science, 2021)
In the Space@Sea project a conceptual study is performed to develop standardized cost efficient floating modular islands with low environmental impact. As these floating modular islands are introduced for a purpose which is likely to determine the environmental impact, possible applications were considered: living, aquaculture, ports and logistics, and energy hub. The aim of this study is to develop a structured approach for Environmental Impact Assessments (EIAs) of floating modular islands and their applications as these are considered within the Space@Sea project. To contribute to the efficiency and sustainability of future floating island developments, early awareness of the likely environmental consequences is important and requires a solid knowledge base. To that end we recommend a screening approach to identify the main threats to the marine ecosystem and their potential impacts at the earliest (conceptual) stage of development. For each Space@Sea type of application, this screening approach should identify the main threats through an EIA that links critical pressures with sensitive ecosystem components. While conventional impact assessments only consider negative impacts, we also consider potential environmental benefits of floating islands. This not only to enhance more environmental-friendly designs but also to provide a balanced perspective which considers not only threats but also opportunities in future developments and implementation of floating islands and their applications.